Influence of Low Self-Esteem Due To Teenage Pregnancy on Educational Performance among Pregnant Teenagers in Secondary Schools in Narok County - Cherotich, Daisy; Kiptiony, Gladys; Kay, James (East African Journal of Humanities and Social Sciences, 2022)
The aim of this paper was to establish the influence of low self-esteem due to teenage pregnancy on educational performance among pregnant teenagers in secondary schools in Narok County. The study was backed by the human capital theory and self-efficacy theory. The study adopted the Expost Facto research design. The Target population was pregnant teenagers in public secondary schools in Narok County, Kenya. The study was conducted in 78 secondary schools, with a population of 156 pregnant teenagers in schools from which as a sample size of 132 pregnant teenagers and 66 guidance and counseling teachers was drawn. Data was collected using questionnaires and interview schedules. Piloting of instruments was done in 7 public secondary schools (10 percent of the sample size in Narok County. Validity check was done with the help of supervisors, and a reliability Cronbach coefficient of 0. 743 was achieved. The study computed descriptive statistics such as frequency means and percentages using SPSS 25 and presented using Tables and charts. Qualitative data was analyzed using a thematic analysis approach and presented using narrations. The study established that low self-esteem due to teenage pregnancy has a statistically insignificant negative influence on educational performance among pregnant teenagers in secondary schools. The study recommended that: The Ministry of Education should consider reviewing the policy relating to teenage program, such that pregnant teenagers are allowed to go home and come back to school after giving birth. Contextual barriers that may hinder pregnant teenagers exercising their right to education need to attended to, and further collaboration between the school management and the community leadership fostered, so that boyfriends and parents also benefit from the G/C arrangements. The Ministry of Education’s stakeholders may refer to these findings as a guide for updating and/or implementing relevant policies geared towards controlling of role of psychological constructs on educational performance among pregnant teenagers.
Keywords: Low Self-Esteem; Teenage Pregnancy; Educational Performance